2008
DOI: 10.1021/cm800781t
|View full text |Cite
|
Sign up to set email alerts
|

Hydration/Dehydration and Cation Migration Processes at High Temperature in Zeolite Chabazite

Abstract: High temperature structural behavior of a natural chabazite of composition (Ca 1.1 Na 0.4 K 0.7 )-[Si 8.6 Al 3.4 O 24 ] • 14.4H 2 O has been characterized by means of in situ HT single-crystal X-ray diffraction (SC-XRD) and thermogravimetric analysis. Lattice dimensions have been measured in the 25-700 °C range and crystal structure refined from XRD data collected at T ) 25, 100, 125, 175, 250, 300, 425, and 600 °C. Variations of unit-cell parameters as a function of temperature reveal two discontinuities at 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 34 publications
2
16
0
Order By: Relevance
“…It can be observed that the mass of all three materials decreased with increased temperature, which is attributed to the progressive removal of water molecules from different crystallographic sites. As shown in the works on natural chabazites by Fialips and Zema, different energetic types of water exist in these materials [36,37]. In all samples, dehydration began as soon as the temperature was raised, however the thermal stability and mass variations are different for each material.…”
Section: Thermal Stability Of the Synthesized Chabazite Powdersmentioning
confidence: 84%
“…It can be observed that the mass of all three materials decreased with increased temperature, which is attributed to the progressive removal of water molecules from different crystallographic sites. As shown in the works on natural chabazites by Fialips and Zema, different energetic types of water exist in these materials [36,37]. In all samples, dehydration began as soon as the temperature was raised, however the thermal stability and mass variations are different for each material.…”
Section: Thermal Stability Of the Synthesized Chabazite Powdersmentioning
confidence: 84%
“…Without knowing the chemical composition of the Monte Somma chabazite, and considering the weak intensity of X-ray reflections of the subordinate chabazite phase, the interpretations of extra-framework occupants have only a semiquantitative character. At 50ºC the major cation site C2 (Zema et al, 2008) crowns on the sixmembered ring of tetrahedra, while the opposite side is shielded by H 2 O. Note that this site was split into K1, K2 and Na2 subsites by Yakubovich et al (2005).…”
Section: Temperature-dependent Distortion In Chabazite Inclusionsmentioning
confidence: 99%
“…Note that this site was split into K1, K2 and Na2 subsites by Yakubovich et al (2005). The centres of eight-membered rings are plugged by the low-occupancy C5 site (labelled according to Zema et al, 2008). At 125ºC, the main part of H 2 O coordinating C2 is released and C2 moves closer to the centre of a six-membered ring; the occupancy of C5 FIG.…”
Section: Temperature-dependent Distortion In Chabazite Inclusionsmentioning
confidence: 99%
“…Although there are some inorganic oxides that exhibit small volume changes 18 19 20 21 22 . Chabazite, one of the most widespread natural zeolites and one of the first zeolites to be studied for a wide range of industrial and technological applications, showed a volume change of 0.1% after high-temperature treatment (873 K) 22 . The key building blocks of the crystal shown here are the doughnut-shaped inorganic molecular metal oxide rings, [P 8 W 48 O 184 ] 40− ({P 8 W 48 }), connected to each other by dicationic cobalt linkers to form a lattice 23 .…”
mentioning
confidence: 99%